DIDACTIC BASIS OF ORGANIZING THE EDUCATIONAL PROCESS BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Ergasheva Ra’no Ahadovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This article discusses the didactic foundations of the integration of artificial intelligence technologies into the educational process, the need to reconsider the purpose, content, methods, tools and results of teaching in the context of the digital transformation of the modern educational paradigm, the didactic principles of organizing education based on artificial intelligence, including flexibility, individualization, interactivity, data-based decision-making and automated analysis of the pedagogical process. It also discusses the role of AI tools in the activities of a teacher, ethical and methodological issues in their application, as well as the need to develop digital pedagogical competencies. The author argues that artificial intelligence is a strategic tool for humanizing the educational process and deepening subject-subject relations between teachers and students.